Transformative Education at Nurul Haramain Nahdlatul Wathan Narmada Pesantren West Lombok and Thohir Yasin Lendang Nangka Pesantren East Lombok - Suryawan, Muhammad Hasan; Zainuddin, Muhammad; Walid, Muhammad; Barizi, Ahmad (Riviera Publishing, 2024)
Islamic boarding schools, as educational institutions oriented to the needs of the community, need to adapt to social changes due to the development of the times and technology. This research aims to explore scientific development, institutional transformation, learning innovation, and transformation results in Nurul Haramaian NW Narmada Islamic Boarding School and Thohir Yasin Lendang Nangka Islamic Boarding School. A qualitative approach with field research methods was used to compare the two pesantren that seek to make social change through transformative education. The results of the study show that the development of science in the two pesantren includes a comprehensive methodology that is internalized in religious and general subjects, as well as extracurricular activities in Nurul Haramaian. The institutional transformation includes establishing formal and non-formal institutions and changes in education and curriculum management. Learning innovation involves the use of information technology and the development of learning methods that are by the character of the pesantren. From the results of the transformation, graduates of the two Islamic boarding schools showed comprehensive knowledge, skills, and good morals and had a positive impact on society, especially in economic and social aspects. This research emphasizes the importance of scientific development, institutional transformation, and educational innovation to maintain the existence of Islamic boarding schools as transformative institutions that contribute to social change.